Epistemological divergences in the approach of the theoretical framework in university theses - Munguía Becerra, Paul (2020)
This paper proposes a meta-research of the Social Communication theses of a public university. Its mainobjective is to analyze the epistemological foundations of the theoretical framework and its methodologicalapproach in social communication theses. It sets as its specific objectives: a) to identify trends in themethodological characteristics of the theses and b) to examine the distinctive features of the formulationof the theoretical framework of the theses. The research is exploratory-descriptive, non-experimental, empirical, and quantitative, and it uses the technique of content analysis. The results show the frequencies ofeleven categories of analysis. The study reveals a significant epistemological divergence with researches thatdo not have theoretical framework. Similarly, when the content of the theses is reviewed, 50% of them carry out a thematic content, which is not supported by a paradigm or a communication approach. This, in spite of the fact that 70% of the theses include textbooks of theories in the bibliography.